VSC-HVDC and Its Applications for Black Start Restoration Processes - Rafael Sanchez Garciarivas; Diego Rasilla Gonzalez; Javier Agustin Navarro; Luis Arturo Soriano; José de Jesús Rubio; Maria Victoria Gomez; Victor Garcia; Jaime Pacheco (Applied Sciences, 2021)
System reliability is a measure of an electric grid system’s ability to deliver uninterrupted service at the proper voltage and frequency. This property of the electric system is commonly affected by critical processes, such as a total blackout. The electric system restoration is a complex process which consists of returning generators, transmission system elements, and restoring load following an outage of the electric system. However, the absence of a generator or unit of black start capabilities may worsen the duration and effects of blackouts, having severe consequences. Black start capability is important as it can reduce the interruption time, decrease the economic loss, and restart the power supply fast and efficiently. In recent years, several works have reported advances about the High Voltage Direct Current (HVDC) technology based on the Voltage-Source Converter (VSC) as an attractive and promising technology to increase black start capability. This paper is a review of the current studies of VSC-HVDC as black start power and discusses the advantages and limitations of recent methods. The major points addressed in this paper are as follows: the current theoretical approach of the black start process and the used HVDC technologies, the advantages of VSC-HVDC as black start power, a compressive review of the literature about the black start capabilities using VSC-HVDC technologies, and a description of the main methods recently used to provide an enhancement for restoration processes. Finally, this paper discusses new challenges and perspectives for VSC-HVDC links in order to provide an enhancement for restoration processes.